Counseling on leadership and innovative behavior for women’s groups assisted by the Cempaka Wangi Foundation, Bintaro - B. Medina Nilasari; Lydia Rosintan Simanjuntak; Ngesti Andik Rimbawanto; Ulfi Naria Rahmawati (Universitas Muhammadiyah Magelang, 2023)
For women who are also mothers, especially those with low education, trading is an alternative job that generates money. Without innovation, it is certain that consumers will quickly get bored and their business will sink in the midst of hectic competition. Therefore, efforts to foster innovative behavior in the family are leadership, especially transformational. This is because a transformational leader can create attitudes and conditions that evoke the innovative behavior of his followers and thus achieve the desired creative results. Based on the problems in the group of mothers assisted by the Cempaka Wangi Foundation in Bintaro, South Jakarta, the purpose of this service is to help mothers foster innovative family behavior. The method used is counseling about the role of leadership and innovation in the family. Based on the evaluation results, all participants stated that their understanding of leadership and innovation had increased.